2020
DOI: 10.1111/fwb.13602
|View full text |Cite
|
Sign up to set email alerts
|

Design features of constructed floodplain ponds influence waterbird and fish communities in northern New Zealand

Abstract: 1. Ponds can provide important refuges for aquatic biota on developed floodplains and are increasingly being constructed in an effort to enhance native biodiversity and ecosystem services in degraded landscapes. This study examined 34 constructed ponds to investigate the influence of design features on community composition, native biodiversity, and the biomass or abundance of common fish and waterbirds on the lower Waikato River floodplain, northern New Zealand. 2. Inundation frequency appeared to be a key fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Therefore, combined with the requirement for stormwater runoff (Malaviya and Singh, 2012 ) or pollution abatement efficiency (Nivala et al., 2018 ), wetland construction must integrate more ecosystem services (Kim et al., 2011 ). For improved waterbird conservation, we suggest that future studies should aim to quantify the appropriate wetland area, according to waterbird composition characteristics and their life history, to determine the smallest area necessary for constructing artificial wetlands in given regions (Garrett‐Walker et al., 2020 ). Moreover, vegetation configuration, which affects waterbird composition (Wang et al, 2020 ), usually varies with ecological succession.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, combined with the requirement for stormwater runoff (Malaviya and Singh, 2012 ) or pollution abatement efficiency (Nivala et al., 2018 ), wetland construction must integrate more ecosystem services (Kim et al., 2011 ). For improved waterbird conservation, we suggest that future studies should aim to quantify the appropriate wetland area, according to waterbird composition characteristics and their life history, to determine the smallest area necessary for constructing artificial wetlands in given regions (Garrett‐Walker et al., 2020 ). Moreover, vegetation configuration, which affects waterbird composition (Wang et al, 2020 ), usually varies with ecological succession.…”
Section: Discussionmentioning
confidence: 99%
“…(2016), and Garrett‐Walker et al. (2020), respectively. Data presented in Figures 1 and 5 are publicly available from Waikato Regional Council, Hamilton, New Zealand (https://www.waikatoregion.govt.nz/).…”
Section: Data Availability Statementmentioning
confidence: 97%
“…Garrett‐Walker et al. (2020) identified several design features of LWRF constructed ponds influencing the fish community structure and the abundance or biomass of particular species, including landscape position, the area of islands, depth regimes and riparian vegetation composition. Connectivity in the form of inundation frequency had positive effects on invasive carp, goldfish and brown bullhead, and negative effects on gambusia abundance.…”
Section: Regaining Floodplain Resilience To Sustain Native Fisheriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Now we have some experience of water replenishment of the floodplains outside residential areas, in the work by [Chen et al, 2020] presented the observations results of the replenishment impact on the Zhalong wetland (China), the biodiversity increased over 19 years, the assessment of water balance components showed that 64% of biomass growth was formed in the summer months due to precipitation, 25% due to water replenishment and 11% due to river flooding, the frequency of the water replenishment affected biodiversity. In the work by [Garrett-Walker et al 2020] it was also emphasized that the biodiversity of the floodplain lake was affected by flooding intensity and the waterbody size, the biodiversity increased if the area of the lake was more than 1.0 ha and the lake perimeter was more than 800 meters. The observations of the water quality in the oxbow lakes, which were connected and isolated from the river, during the vegetation season were carried out by [Wang et al 2020], the study showed that isolated oxbow lakes had higher concentrations of dissolved oxygen and nutrients, which led to eutrophication of the lakes, at the same time water quality significantly improved in lakes after the floods, which indicates the positive impact of the water replenishment.…”
Section: Introductionmentioning
confidence: 99%